Pengaduk Pakan Ayam Otomatis Berbasis IoT - Nabila Patawa Siregar; Pristisal Wibowo; Ahmad Dani (Jurnal Nasional Teknologi Komputer, 2026)
The development of Internet of Things (IoT) technology has significantly influenced the livestock sector, particularly in improving the efficiency of feed management in poultry farming. Manual feed mixing is still widely applied, despite its limitations in terms of time, labor, and feed uniformity. This study aims to design and evaluate the performance of an IoT-based automatic chicken feed mixing system to enhance operational efficiency and real-time monitoring. The research employs a quantitative experimental approach based on system simulation, including hardware and software design, system modeling, and functional performance testing. The system is controlled by an ESP32 microcontroller integrated with a DC motor, servo motor, relay, and an IoT-based monitoring application. Experimental results indicate that the system operates stably under various feed load conditions, with relatively constant motor voltage and power consumption increasing proportionally with the applied load. Energy consumption remains within an efficient range, while the IoT application successfully provides real-time system status monitoring with responsive performance. Overall, the proposed IoT-based automatic feed mixing system effectively improves feed processing efficiency, reduces dependence on manual labor, and supports the implementation of modern, technology-driven poultry farming systems.